Clurut Commander in the Movement to Defend Independence in Tengaran 1947-1949 - Safi'i, Muhammad (Journal of Islamic History, 2024)
After Indonesia's independence on August 17, 1945, the challenge of struggle continued, not least because the Dutch again wanted to control the natural resources in Indonesia. Physical battles were inevitable in various regions, Kiai, local troops (clurut troops), and the TNI fought and defended the independence of Indonesia. In 1947-1949 in Tengaran Subdistrict with great effort and success. This cannot be separated from the support of KH. Mawardi and the kiai who trained the Clurut Troops as the frontline in defending the Tengaran area. This research is an analytical descriptive study to find out the role of KH. Mawardi more deeply. This research uses historical research methods, namely: Heuristic stages of collecting sources, verification or criticism of sources, Interpretation or interpretation, and historiography or historical writing. Then the use of data related to the theme raised is primary source data and secondary sources and the same literature. Data collection by researchers is carried out by interviews, literature studies and document studies. From the results of research and analysis of sources obtained by researchers, as well as field results. KH. Mawardi's role began when the headquarters in Petak, Susukan was bombed during military aggression. The search for a new headquarters began and moved to Tengaran. The formation of the Clurut troops resulted from the gathering of the kiai and KH. Mawardi to prepare for defense and seek information from the Dutch. Clurut troops from among the youth began to join when KH. Mawardi preached at the Tengaran mosque, in daily life equipped with moral values and weapons training in preparation for the struggle against the Dutch.